Calculating Parameters for Se and Tin Plasmas Produced by Pulsed Nd: YAG Laser - Saeed, Zahraa A.; Aadim, Kadhim A. (Iraqi Journal of Science, 2023)
In this study, the plasma formed by the preparation of Se and Tin (Sn) using a Nd: YAG laser with a wavelength of 1064 nm in air, which was then studied using the technique of optical emission spectrum, was presented (OES).The laser-induced plasma parameters such an electron temperature (Te) were identified using two-ratio methods, using Stark broadening methods to determine the density of electrons (ne). According to the findings, there is a correlation between the amount of laser energy that is applied and the increase in the emission intensity of the spectral lines. In the case of Se plasma, an increase in laser energy causes a rise in the temperature of the electrons. While increasing the temperature of the electrons by increasing the amount of laser energy, the temperature of the Sn plasma gradually lowers. By increasing the laser energy, the electron density of both selenium (Se) and tin (Sn) can be increased. In addition, the parameters of the plasma were discovered. Such parameters as the Debye length (λD), plasma frequency (Fp), and Debye Number (ND).